Long-Term Clinical Outcomes of Radical Prostatectomy versus Watchful Waiting in Localized Prostate Cancer Patients: A Systematic Review and Meta-Analysis - Mojtaba NOUHI; Seyed Masood MOUSAVI; Alireza OLYAEEMANESH; Nasser SHAKSISALIM; Ali AKBARI SARI (Tehran University of Medical Sciences, 2019)
Background: The present study aimed to compare the long-term clinical and functional outcomes of patients with clinically localized prostate cancer treated with radical prostatectomy compared to the watchful waiting. Methods: PubMed, Cochrane Central Register of Controlled Trials and reference lists of relevant marker studies were scrutinized from inception to Jan 2018. Two reviewers conducted data abstraction and quality assessment of included trials independently. Quality of included studies were assessed by using Cochrane checklist. Inverse-variance and Mantel-Haenszel estimates under random effects model were used to pool results as relative risks with 95% confidence interval. Heterogeneity was assessed by using I2. Results: Three randomized controlled trials with 1568 participants were included. Compared to watchful waiting, radical prostatectomy had no significant effect on all-cause mortality at 12-year follow-up. However, radical prostatectomy had significant effect on reducing prostate-cause mortality at 12-year follow-up. We found significant lower prostate-cause mortality in patients with PSA>10 and GS≥7 scores who had undergone radical prostatectomy compared with patients in watchful waiting group. In addition, younger patients undergoing surgery developed lower distant metastases rate compared to another approach. Watchful waiting had a significant effect on erectile and urinary incontinence during 2 years. Conclusion: There was no significant difference between radical prostatectomy and watchful waiting on all-cause mortality. However, the radical prostatectomy was associated with statistically lower prostate-cause mortality and metastases rates. Compared with older men, younger men experienced better clinical outcomes. Moreover, watchful waiting had better effect on reducing erectile dysfunction and urinary incontinence among patients during 2 years compared to radical prostatectomy.